Alpha and gamma tocopherol metabolism in healthy subjects and patients with end-stage renal disease - Himmelfarb, Jonathan; Kane, Jane; Mcmonagle, Ellen; Zaltas, Eric; Bobzin, Steve; Boddupalli, Sekhar; Phinney, Stephen; Miller, Guy (Kidney international, 2003)
Alpha and gamma tocopherol metabolism in healthy subjects and patients with end-stage renal disease. The metabolism of alpha and gamma tocopherol, the major components of vitamin E, have not been studied in uremic patients. The major pathway of tocopherol metabolism is via phytyl side chain oxidation, leaving carboxyethyl-hydroxychromans (CEHC) as metabolites. Alpha and gamma CEHC are water soluble, renally excreted, with known potent anti-inflammatory and antioxidative properties. We examined serum alpha and gamma tocopherol and respective CEHC concentrations in 15 healthy subjects and 15 chronic hemodialysis patients. Serum alpha tocopherol levels were similar in hemodialysis patients (12.03 ± 1.34 μg/mL) and healthy subjects (11.21 ± 0.20 μg/mL), while serum gamma tocopherol levels were significantly greater in hemodialysis patients (3.17 ± 0.37 μg/mL) compared to healthy subjects (1.08 ± 0.06 μg/mL, P < 0.0001). Serum alpha and gamma CEHC levels were tenfold and sixfold higher in hemodialysis patients compared to healthy subjects, respectively (both P < 0.0001). Serum alpha and gamma tocopherol levels and CEHC metabolites were also measured after supplementation of alpha- or gamma-enriched mixed tocopherols in both hemodialysis patients and healthy subjects. Tocopherol administration resulted in modest or nonsignificant changes in serum tocopherol concentrations, while markedly increasing serum CEHC concentrations in both healthy subjects and hemodialysis patients. Hemodialysis resulted in no change in the serum alpha or gamma tocopherol concentrations while decreasing serum alpha CEHC and gamma CEHC levels by 63% and 53%, respectively (both P = 0.001 versus predialysis). Fourteen-day administration of gamma-enriched but not alpha tocopherols lowered median C-reactive protein (CRP) significantly in hemodialysis patients (4.4 to 2.1mg/L, P < 0.02). First, serum alpha and gamma CEHC accumulate in uremic patients compared to healthy subjects; second, supplementation with tocopherols dramatically increases serum CEHC levels in both healthy subjects and hemodialysis patients; and, finally, CEHC accumulation may mediate anti-inflammatory and antioxidative effects of tocopherols in hemodialysis patients.